Integrating TAM, IDT and Service Quality to Explain Mobile Banking Adoption in Cambodia: A PLS-SEM Approach - Ratha Seng; Dr. Rady Chhun; Dr. Seng Tha Chay; Dr. Bunnak Poch (jfpublisher, 2026)
Mobile banking is expected to cause a significant digital transformation in Cambodia, a nation commonly known for its reliance on cash transactions. This research addresses the need to determine the factors influencing Cambodians' readiness to adopt mobile banking services. Specifically, the study aims to investigate whether the relationship between core constructs including Perceived Usefulness, Perceived Ease of Use, Relative Advantage, Compatibility, Complexity, Trust, Security, Service Quality, and Customer Satisfaction with consumers’ behavioral intention to adopt mobile banking. The research employs an integrated theoretical framework combining the Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT), and Service Quality. Data were collected through an online survey from 528 university students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical findings reveal that Trust, Security, Perceived Ease of Use (PEOU), and Customer Satisfaction are the most significant positive determinants of behavioral intention to adopt mobile banking. In contrast, Perceived Usefulness and Complexity did not demonstrate a direct, significant influence on Behavioral Intention within this context. The study concludes that the integrated model is robust, providing critical insights for Cambodian financial institutions, which should strategically prioritize enhancing security features, building user trust, and focusing on intuitive and easy-to-use interfaces to accelerate the digital transformation of financial services.